Investigating Drug Diffusion Using Multi-Compartment Model - Sana Fadil; Guzlan Miskeen; Ahlam Alhadi (African Journal of Advanced Pure and Applied Sciences, 2024)
Compartment models play a central role in modeling drug diffusion in pharmacokinetics. Multi-compartment models are mathematical representations used to explain the mechanisms of drug distribution and elimination. The study aims to employ multi-compartmental models represented by three and four compartments in order to comprehend drug behavior in the body. Pharmacokinetic parameters were determined for two cases of experimental drug concentration data. The models were implemented by solving differential equations that represent the system of three and four compartments and then estimating pharmacokinetic parameters. These work utilize a graphical user interface (GUI) to facilitate entering data ad presenting the corresponding results. The least squares method was employed to fit the experimental data with the estimated ones. The study concluded that the accuracy of the obtained mathematical model depends on the quality of the input data. Moreover, the four-compartment model had the lowest error rate, indicating the best fit in both cases.